A Day in Algonquin Park: William W. H. Gunn and the circadian audio portrait. Issue 2 (12th July 2017) - Cameron, Laura; Rogalsky, Matt
Abstract : This article considers the place of William W. H. 'Bill' Gunn in the history of electroacoustic music with a focus on one of his earliest creative forays, the 1955 production of A Day in Algonquin Park, a composition in the genre of what the authors have dubbed the circadian audio portrait . In exploring Gunn's compositional decisions and the political and creative contexts which surrounded them, we detail his sonic practice and make the argument that Gunn was a soundscape composer before the term was coined, a forerunner of the genre indebted to composers connected with the World Soundscape Project. In doing so, we must acknowledge the ways in which the album's creation and reception play out paradoxical aspects of the wilderness myth, while feeding into the construction of a popular and idealised Canadian identity. We also find his modernist ecological sensibility struggling to articulate a place for human visitors within nature: in this, Gunn's outlook and concerns were not very different from some contemporary soundscape composers. However, this study goes beyond acknowledging a previously 'unknown father' of familiar sounds and debates; in contextualising his work with environmental sound as a contribution to the genre of the circadian audio portrait, we highlight an alternative genealogy for contemporary soundscape composition.